Management of Education Character of Religious Values at Tunas Harapan Kindergarten - Widiatsih, Asri; Nafila Maulida, Ava; Harun, Makmur; Muarif, Syamsul (CV Kalimasada Group, 2025)
Character education is an important component in the formation of early childhood personality. This study aims to examine the management of character education based on religious values ​​in Tunas Harapan Kindergarten, Jember Regency. This process is implemented through natural material collage art activities with star patterns, which focus on the religious values ​​of the first principle of Pancasila, namely Belief in the Almighty God. The researcher used a qualitative approach in this study. Data collection was carried out using interview techniques, observation, and documentation studies. The role of the teacher as a facilitator is very visible in providing direction, instilling values, and encouraging cooperation among children. The results of this observation indicate that the planning, organization, implementation, and evaluation of activities were effective, despite challenges such as limited time and abstract understanding of symbols for children. Supporting factors include children's enthusiasm, school support, and a positive environment. Children succeeded in understanding religious values, showing creativity, and building character, such as discipline, cooperation, and environmental awareness. The evaluation of the activity showed satisfactory results, with positive feedback from children. This study confirms the importance of integrating religious values ​​in early childhood character education through a creative and contextual approach.